CLIENTS AS TEACHERS: THE 7 QUALITIES MOST DESIRED IN A THERAPIST - Ward, Rachel; Morgan, Nancy (PEOPLE: International Journal of Social Sciences, 2017)
Little previous research has directly asked clients to identify the qualities they most desire in a therapist. The current study took place over the summer of 2016 utilizing a questionnaire format that asked over 120 individuals receiving out-patient and residential clinical therapeutic services, to identify the top seven qualities they most desired in a therapist. Participants chose from a list of 33 client-generated adjectives derived from an original focus group of partial-hospitalization and intensive outpatient therapy clients. This study’s participants had the opportunity to also identify and add qualities that were not listed among the original 33 options provided. The study found that clients most valued qualities that can be developed through Mindfulness practices, shedding light on an under-emphasized, but potentially rich area of development in the conception of graduate psychology training curricula. The research outcomes identified domains that, from a client-centered perspective, enhance clients’ engagement in therapy, decrease and repair therapeutic ruptures, and advance the field’s understanding of how therapeutic interventions are most effectively delivered.